2013
DOI: 10.1038/hdy.2013.37
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of effective population size in continuously distributed populations: there goes the neighborhood

Abstract: Use of genetic methods to estimate effective population size (N e ) is rapidly increasing, but all approaches make simplifying assumptions unlikely to be met in real populations. In particular, all assume a single, unstructured population, and none has been evaluated for use with continuously distributed species. We simulated continuous populations with local mating structure, as envisioned by Wright's concept of neighborhood size (NS), and evaluated performance of a single-sample estimator based on linkage di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
169
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 71 publications
4
169
1
3
Order By: Relevance
“…Population structure As population structure can cause inaccuracies in N e estimation (Waples and England, 2011;Neel et al, 2013;Gilbert and Whitlock, 2015), we used two approaches to test for the presence of cryptic population structure within the study area. Arguably the most versatile tests of population structure need not rely on knowledge of where individuals were sampled.…”
Section: Temporal Patternsmentioning
confidence: 99%
“…Population structure As population structure can cause inaccuracies in N e estimation (Waples and England, 2011;Neel et al, 2013;Gilbert and Whitlock, 2015), we used two approaches to test for the presence of cryptic population structure within the study area. Arguably the most versatile tests of population structure need not rely on knowledge of where individuals were sampled.…”
Section: Temporal Patternsmentioning
confidence: 99%
“…N e is the effective number of individuals within the whole population, defined as the size of an ideal population affected by random genetic sampling at the same rate as the population being studied (Wright, 1931(Wright, ,1938, whereas N n is the effective number of individuals within an area of a population (the neighborhood) defined such that the parents of a focal individual can be considered to be genetically representative of the neighborhood's occupants (Wright, 1946). To avoid confusion, the notation N n is used for the neighborhood number instead of N b (Slatkin and Barton, 1989) as N b has been used for the effective number of breeders in a given year in species with overlapping generations (Waples, 2005), and, more generally, for the effective number of parents producing the sample used in the estimation of N e when there is temporal or spatial population structure (Neel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During the initial nonequilibrium phase (he used the first 15 generations), while the genetic structure was being established, estimates of N e (using the decline in heterozygosity) were closely related to N n , but later, when the genetic structure of the population had equilibrated, the estimates of N e were more influenced by N. However, Kawata (1995) found that at these late stages the estimated N e was always less than or equal to the population size, a result conflicting with Equation (4). Neel et al (2013) also simulated a neighborhood-structured population, estimating N e with a single-sample estimator (based on linkage disequilibrium). Like Kawata (1995), they found that under some conditions (in their case, when the genetic sampling was at the scale of a single neighborhood) the estimated N e was close to N n .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations